ANALYSIS OF PENGGARON BUS STATION FACILITIES CITY OF SEMARANG - Christ Prima Sedaya; Susi Sulandari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
City Of Semarang is a capital city of Central Java Province that have 4 bus station in every corner of direction like Mangkang Bus Station in west,Penggaron Bus Station in east,Teroboyo Bus Station in north,and Banyumanik Bus Station in south.Since 1 September 2018, Teroboyo Bus Station was closed due to poor conditions. Therefore, as a researcher interested in seeing the readiness of the Bus Station to face the removal of passengers from the Teroboyo Bus Station in terms of terminal support facilities. One of research is the management of facilities at the Penggaron Bus Station. This research Result is to know how managing facilities at the Penggaron Bus Station The method used here is a qualitative research method. Data collection techniques are questionnaire, observation and documentation techniques in the form of documents or archives from the Ministry of Transportation of the City of Semarang and statistical data on the Penggaron Terminal. The research results at the Penggaron Terminal will show that the facilities at the Penggaron Bus Station have not been maximized, such as seating in the passenger waiting room don’t have a backrest, poor passenger toilet conditions, location of the mosque is not strategic, BRT (Bus Rapid Transit ) Trans Semarang shelter in quite poor condition, and SPBG (Gas Refueling Stations) that have not yet been opened for public.